Streptococcus mutans GlnK protein: an unusual PII family member - Portugal,M.E.G. (2011)
Streptococcus mutans is a Gram-positive bacterium present in the oral cavity, and is considered to be one of the leading causes of dental caries. S. mutans has a glnK gene, which codes for a PII-like protein that is possibly involved in the integration of carbon, nitrogen and energy metabolism in several organisms. To characterize the GlnK protein of S. mutans, the glnK gene was amplified by PCR, and cloned into the expression vectors pET29a(+) and pET28b(+). The native GlnK-Sm was purified by anion exchange (Q-Sepharose) and affinity (Hi-Trap Heparin) chromatography. The GlnK-His-Sm protein was purified using a Hi-Trap Chelating-Ni2+ column. The molecular mass of the GlnK-His-Sm proteins was 85 kDa as determined by gel filtration, indicating that this protein is a hexamer in solution. The GlnK-His-Sm protein is not uridylylated by the Escherichia coli GlnD protein. The activities of the GlnK-Sm and GlnK-His-Sm proteins were assayed in E. coli constitutively expressing the Klebsiella pneumoniae nifLA operon. In K. pneumoniae, NifL inhibits NifA activity in the presence of high ammonium levels and the GlnK protein is required to reduce the inhibition of NifL in the presence of low ammonium levels. The GlnK-Sm protein was unable to reduce NifL inhibition of NifA protein. Surprisingly, the GlnK-His-Sm protein was able to partially reduce NifL inhibition of the NifA protein under nitrogen-limiting conditions, in a manner similar to the GlnK protein of E. coli. These results suggested that S. mutans GlnK is functionally different from E. coli PII proteins.